'Headhunters under the Stars and Stripes': revisiting colonial historiography. (1st October 2020) - Scheerer, Richard G.
ABSTRACT: In 1908, Dean C. Worcester, Secretary of the Interior for the Philippine colonial government, published an article in the New York Times lauding the results of the American government's efforts to advance the conditions of the Philippine 'wild tribes'. Titled 'Headhunters Under the Stars and Stripes', Worcester's article summarized the colonial government's 'civilizing efforts' and the 'astonishing' progress which in just a few years led to a 'degree of self-government' for the non-Christian tribes of the Cordillera. This paper revisits that article and the historical basis for Worcester's claims. Criticism of colonial historiography has, with justification, centred on the colonizers' attempts at embellishing their accomplishments while hiding the less laudatory means and results of the colonization. With the gift of hindsight, I analyse Worcester's narrative for both its accuracy and intent. I find that, while imperfect, his narration is generally accurate as history, and most of his self-congratulation was warranted based on a significant improvement in the living conditions of the indigenous people of the Cordillera. His intent, however, remains controversial. This article discusses his espousal of a Christian/non-Christian animus as the basis for denying Philippine independence.